2019
DOI: 10.1186/s40246-019-0215-5
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of rare genetic diseases—experiences from India

Abstract: Home to a culturally heterogeneous population, India is also a melting pot of genetic diversity. The population architecture characterized by multiple endogamous groups with specific marriage patterns, including the widely prevalent practice of consanguinity, not only makes the Indian population distinct from rest of the world but also provides a unique advantage and niche to understand genetic diseases. Centuries of genetic isolation of population groups have amplified the founder effects, contributing to hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 175 publications
(152 reference statements)
0
23
0
1
Order By: Relevance
“…These rare/unique variations amplify as founder mutations within specific endogamous populations, which in due course translates to population specific genetic diseases. It is estimated that ∼70 million people in India are affected by genetic diseases with about 64 out of 1000 live births carrying disorders such as primary immunodeficiencies, lysosomal storage disorders, mitochondrial diseases, cardiac disorders and muscle-related disorders ( 5 ). The government of India is now focusing on effective cataloging of the genomic variants specific for the Indian population so as to create a blueprint for identification of disease epidemiology, population-specific variants and pharmacogenomic markers ultimately leading to the development of effective therapies for treating genetic disorders ( https://pib.gov.in/PressReleseDetailm.aspx?PRID=1605509 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These rare/unique variations amplify as founder mutations within specific endogamous populations, which in due course translates to population specific genetic diseases. It is estimated that ∼70 million people in India are affected by genetic diseases with about 64 out of 1000 live births carrying disorders such as primary immunodeficiencies, lysosomal storage disorders, mitochondrial diseases, cardiac disorders and muscle-related disorders ( 5 ). The government of India is now focusing on effective cataloging of the genomic variants specific for the Indian population so as to create a blueprint for identification of disease epidemiology, population-specific variants and pharmacogenomic markers ultimately leading to the development of effective therapies for treating genetic disorders ( https://pib.gov.in/PressReleseDetailm.aspx?PRID=1605509 ).…”
Section: Discussionmentioning
confidence: 99%
“…This has resulted in high prevalence of recessive alleles in the Indian population. In the absence of large-scale whole genome studies from India, these sub-population-specific genetic variants are also not adequately captured and catalogued in global medical literature ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The high burden of monogenic disorders is well described in the Indian population (Kaur & Singh, 2010; Sachdeva et al, 2012; Singh et al, 2010; Sivasubbu & Scaria, 2019; Venugopal et al, 2018). However, the incidence and prevalence and consequently the carrier frequencies for most disorders remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Carrier screening was mostly carried out in couples with a previous history of putative recessive disease in the deceased offspring and nonavailability of samples from the proband/s. Globally, thalassemia and structural hemoglobinopathies are the commonest monogenic disorders and India too has a huge burden of these conditions (Colah et al, 2017; Sivasubbu & Scaria, 2019; Williams & Weatherall, 2012). Patients with β thalassemia and sickle cell disease in India are estimated to be 100,000 and 150,000 respectively and the reported average prevalence of carriers for β thalassemia is 3%–4% (Colah et al, 2017) whereas sickle cell disease was observed with a carrier frequency ranging from ~1% to 40% in specific subpopulations in India (Hockham et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Genomic sequencing consortia funded by the government such as GUaRDIAN, (GUaRDIAN Consortium, Sivasubbu, & Scaria, 2019), Indian Genetic Disease Database (IGDD) (Pradhan et al, 2011) are helping us understand the population genetics. Specifically, IGDD website http://www.igdd.iicb.res.in/home.htm enlists the specific mutations found in the Indian population.…”
Section: Databases and Consortiamentioning
confidence: 99%